Computer aided surgery : official journal of the International Society for Computer Aided Surgery - International Society for Computer Aided Surgery (Wiley-Liss, 1997)
Presents "Computer Aided Surgery" (CAS), formerly known as the "Journal of Image Guided Surgery." Notes that CAS publishes articles related to the use of computers and digital technologies in the administration of treatment to patients. Explains that CAS is published six times yearly by John Wiley & Sons, Inc. in New York City, and is the official journal of the International Society for Computer Aided Surgery (ISCAS). Provides a table of contents and abstracts to current and previous issues. Also offers access to the full-text version of the articles only to subscribers with a password. Contains subscription information, along with submission guidelines for prospective authors. Links to the home pages of Wiley and the ISCAS. Posts contact information for the publisher via mailing address, telephone and fax numbers, and e-mail.
Keywords: Imaging systems in medicine : Periodicals; Surgery : Computer simulation : Periodicals; Surgical technology : Periodicals; Medical technology : Periodicals; Surgery, Operative : Periodicals; Image Processing, Computer-Assisted; Surgery, Operative; Therapy, Computer-Assisted; Imagerie médicale : Périodiques; Chirurgie opératoire : Périodiques; Chirurgie : Simulation par ordinateur : Périodiques; Technologie chirurgicale : Périodiques; Technologie médicale : Périodiques; Imaging systems in medicine; Medical technology; Surgery : Computer simulation; Surgical technology; Electronic publications